The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12879-022-07731-6
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic and central nervous system tuberculosis complicated by a paradoxical response manifesting as a spinal tuberculoma: a case report

Abstract: Background The post-partum period is a risk factor for tuberculosis (TB), possibly including the period after miscarriage as illustrated here. This case demonstrates how non-specific symptoms can hide widely disseminated TB. Case presentation A healthy 26-year-old female with a history of recent miscarriage presented to the emergency department with non-specific symptoms of headache, abdominal pain, and sub-acute fevers. She had immigrated to the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…PR is conjectured to represent a delayed local immune response or dysregulation of cellular immune responses to a large number of rapidly killed M. tuberculosis components 7) . Velivela et al reported an increased risk of epidural abscesses with PR in patients with spinal TB, necessitating, as in this case, surgery in half of the cases 8) .…”
mentioning
confidence: 99%
“…PR is conjectured to represent a delayed local immune response or dysregulation of cellular immune responses to a large number of rapidly killed M. tuberculosis components 7) . Velivela et al reported an increased risk of epidural abscesses with PR in patients with spinal TB, necessitating, as in this case, surgery in half of the cases 8) .…”
mentioning
confidence: 99%